Applied Model for Horizontal Well Matrix Acidizing: Model Terapan untuk Pengasaman Matriks Sumur Horisontal - Salam Abdul-Zahra Khalefa; Ali Nooruldeen Abdulkareem; Mudhaffar Yacoub Hussein; Ali Hadi Kareem (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Horizontal wells often exhibit low productivity due to formation damage induced by drilling, work-over, production, and injection operations, which impair the physical integrity around the wellbore. Specific Background: Matrix acidizing has been widely adopted to mitigate such damage, especially in complex horizontal well environments where acid distribution along the wellbore directly influences stimulation effectiveness. The process is particularly intricate in reservoirs with varying geological properties, necessitating a thorough understanding of acid-rock interactions and damage mechanisms. Knowledge Gap: Despite extensive historical use of acidizing since the late 19th century, challenges remain in optimizing acid placement, minimizing formation damage, and enhancing well productivity, especially in heterogeneous reservoirs. Aims: This study investigates the mechanisms of formation damage, evaluates the role of different acid types and additives in carbonate and sandstone reservoirs, and models acid distribution to improve stimulation outcomes in long horizontal wells. Results: The modeling approach effectively simulates acid placement and wormhole formation, demonstrating enhanced productivity and damage mitigation. Historical advancements, from early HCl treatments to modern mud acid applications, were analyzed to contextualize current practices. Novelty: The integration of advanced simulation techniques with an in-depth analysis of acid interactions offers new insights into optimizing matrix acidizing, particularly under variable reservoir conditions. Implications: The findings provide a framework for designing more efficient acidizing treatments, reducing operational costs, and improving hydrocarbon recovery. This research contributes to the broader understanding of formation damage control, guiding future strategies in well stimulation and reservoir management. Highlights: Formation Damage: Causes, impact, and mitigation strategies. Acidizing Process: Optimization of acid placement and additive use. Modeling Approach: Simulates acid flow for better well stimulation. Keywords: Horizontal wells, Formation damage, Matrix acidizing, Acid-rock interaction, Well stimulation